Tingkat pengetahuan dan kebiasaan konsumsi junk food dengan status gizi pada mahasiswa Program Studi Gizi Universitas Siliwangi - Annisa, Maulina; Atmadja, Taufiq Firdaus Al-Ghifari; Susilowati, Prima Endang (Nutrition Scientific Journal, 2022)
Nutritional problems can be caused by the habit of consuming foods high in fat, salt, and sugar and low in vitamins and minerals, or "junk food." The level of knowledge related to junk food also influences perceptions, attitudes, consumption behavior, and consumption habits related to junk food, as well as nutritional status. The aim of the study was to find out the correlation between the level of knowledge and habits of eating junk food and the nutritional status of the 2019 class of Siliwangi University Nutrition Study Program students. The research method is a quantitative analytic survey with a cross-sectional approach. The technique of taking purposive sampling subjects from a population of 71 people and 69 people as research subjects Data collection involves filling out a junk food knowledge test, the Food Frequency Questionnaire (FFQ), and measuring height and weight. Data analysis used the Spearman rank correlation test. The results of the research on the level of knowledge of junk food and nutritional status obtained a significance value of 0.045 (0.05) and a correlation coefficient of 0.242. The significance value of the habit of eating junk food with regard to nutritional status is 0.521 ( 0.05). The conclusion of this study is that there is a moderate or moderately strong relationship between the level of knowledge of junk food and nutritional status, but no relationship between junk food habits and nutritional status. Suggestions include reducing or avoiding consumption of junk food and applying information and knowledge in everyday life so that you have a good nutritional status and avoid the dangers of junk food for your health.Masalah gizi dapat ditimbulkan oleh kebiasaan konsumsi makanan tinggi lemak, garam, gula dan rendah vitamin serta mineral atau disebut junk food. Tingkat pengetahuan terkait junk food juga berpengaruh terhadap persepsi, sikap, perilaku konsumsi dan kebiasaan konsumsi junk food serta status gizi. Tujuan dari penelitian ini adalah untuk mengetahui korelasi antara tingkat pengetahuan dan kebiasaaan konsumsi junk food dengan status gizi mahasiswa angkatan 2019 Program Studi Gizi Universitas Siliwangi. Metode penelitian kuantitatif dengan survei analitik dan Â pendekatan cross sectional. Teknik pengambilan subjek menggunakan seluruh sampel namun dari 71 total populasi hanya 69 subjek yang memenuhi kriteria. Pengambilan data dengan cara pengisian kuesioner tingkat pengetahuan junk food, Food Frequency Questionnare (FFQ), pengukuran tinggi badan dan berat badan. Analisis data menggunakan uji korelasi spearman rank. Hasil penelitian ini yaitu terdapat hubungan antara tingkat pengetahuan junk food dengan status gizi, didapatkan nilai (0,05) sebesar 0.045 dan nilai koefisiensi korelasi 0.242 yang menunjukkan tingkat keeratan hubungan moderat atau sedang. Tidak terdapat hubungan antara kebiasaan makan Â junk food dengan status gizi (0,05) yaitu 0.521.